Cognitive and Initial Psychometric Testing of the Errors of Care Omission Survey: A New Patient Safety Tool for Primary Care - Poghosyan, Lusine (J Nurs Meas, 2019)
BACKGROUND AND PURPOSE: Most patient safety studies focus on errors of commission rather than on errors of omission. No tools measure errors of omission in primary care. We developed the Errors of Care Omission Survey (ECOS) and present its cognitive and psychometric testing. METHODS: Twenty-six primary care providers (PCPs) participated in cognitive interviews, which were audiotaped, transcribed, and analyzed. ECOS was also pilot tested with 37 PCPs. Item analysis and reliability testing w conducted. RESULTS: Interviewees agreed that ECOS measures errors of omission and items were clear. The response categories were revised. All items were correlated and subscales had high internal consistency reliability. CONCLUSIONS: ECOS can measure errors of omission in primary care.